Peran dan Tantangan Jurnalisme Islam dalam Penyampaian Informasi di Era Digital - Fachrur Rizha (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2022)
This article aims to see how the role and challenges of Islamic journalism in conveying information to the public. The method used is library research, so the data used is completely based on library research and primary sources related to the article discussion. The results show that the concept of conveying information in Islamic journalism is to prioritize the truth and accuracy of information and is loaded with Islamic values. The role of Islamic journalism in conveying information includes being critical of the environment, renewing creative and contemporary ideas, maintaining and developing the values of Islamic treasures, and uniting the Muslim community. The challenge faced by Islamic journalism today is that there are still few mass media with Islamic nuances that are able to compete with the general mass media in conveying information to the public.